Adverse Effects of Oseltamivir Phosphate Therapy on the Liver of LDLR−/− Mice Without Any Benefit on Atherosclerosis and Thrombosis. Issue 5 (May 2021) - Bocquet, Olivier; Wahart, Amandine; Sarazin, Thomas; Vincent, Elise; Schneider, Christophe; Fougerat, Anne; Gayral, Stéphanie; Henry, Aubéri; Blaise, Sébastien; Romier-Crouzet, Béatrice; Boulagnon, Camille; Jaisson, Stéphane; et al.
Abstract : Abstract: Desialylation, governed by sialidases or neuraminidases, is strongly implicated in a wide range of human disorders, and accumulative data show that inhibition of neuraminidases, such as neuraminidases 1 sialidase, may be useful for managing atherosclerosis. Several studies have reported promising effects of oseltamivir phosphate, a widely used anti-influenza sialidase inhibitor, on human cancer cells, inflammation, and insulin resistance. In this study, we evaluated the effects of oseltamivir phosphate on atherosclerosis and thrombosis and potential liver toxicity in LDLR −/− mice fed with high-fat diet. Our results showed that oseltamivir phosphate significantly decreased plasma levels of LDL cholesterol and elastin fragmentation in aorta. However, no effect was observed on both atherosclerotic plaque size in aortic roots and chemically induced thrombosis in carotid arteries. Importantly, oseltamivir phosphate administration had adverse effects on the liver of mice and significantly increased messenger RNA expression levels of F4/80, interleukin-1β, transforming growth factor-β1, matrix metalloproteinase-12, and collagen. Taken together, our findings suggest that oseltamivir phosphate has limited benefits on atherosclerosis and carotid thrombosis and may lead to adverse side effects on the liver with increased inflammation and fibrosis.